Enhanced healing of oral chemical burn by inhibiting inflammatory factors with an oral administration of shengFu oil - Xin Yin; Jing Hong; He-Bin Tang; Min Liu; Yu-Sang Li (Frontiers Media S.A., 2022)
ShengFu oil is a compounded Chinese medicinal prescription, and provides antibacterial, anti-inflammatory, and analgesic effects, favoring burn wound repair. In this study, we aimed at investigating the effects of topical applications of ShengFu oil and its active ingredients in oral chemical burns and elucidating its regulatory effects on β-catenin, COX-2, and MMP-9 expression caused by exposure to acid or alkaline agents. ShengFu oil contains 16 components, such as Frankincense, Radix Scutellariae and Radix Rehmanniae, and the main active ingredients from Frankincense are α-pinene, linalool, and n-octanol. Mouse models of oral chemical burns were induced by using glacial acetic acid or sodium hydroxide. Hematoxylin and eosin staining and immunohistochemical staining were used to detect the protein expressions of β-catenin, COX-2, and MMP-9 in wound tissues. They were further quantified by multispectral imaging analysis to clarify the effective mechanism of ShengFu oil for intervening inflammatory factors and active components. Our results indicated that the application of ShengFu oil on oral chemical burns effectively stopped the oral burn bleeding and reduced the inflammatory reaction in the damaged tissues, demonstrating that ShengFu oil can promote wound tissue repair in burns caused by heat, acids, and alkalis. The immunohistochemical staining results illustrated that ShengFu oil and its active ingredients significantly reversed the abnormal changes in inflammation-related proteins in mouse tongue tissues that were caused by chemical burns. Regarding long-term toxic effects of ShengFu oil on the gastrointestinal tract, liver, and kidney system, the results of hematoxylin and eosin staining experiments depicted that ShengFu oil was safe and effective for liver, kidney, intestine, esophagus, and tongue. All of these demonstrated that ShengFu oil and its active ingredients are effective and safe in preventing and treating oral chemical burns by interfering with the inflammatory microenvironment.